Numerical Investigations of Laser Diode End-pumped Solid-state Cr\(^3+\):LiSAF Lasers Passively Q-switched with Cr\(^4+\):YSO Crystal - Hao, Nguyen Van; Minh, Pham Hong; Duong, Pham Van; Hung, Nguyen Dai; Binh, Nguyen The (Communications in Physics, 2016)
We have numerically investigated, for the first time, the optical performance and characteristics of diode-end-pumped passively Cr\(^4+\):YSO Q-switched solid-state Cr\(^3 + \):LiSAF lasers using a rate equation system extended to multi-wavelength. Homogeneously broadened emission spectra of the laser crystal and broad absorption spectra of Cr\(^4+\):YSO saturable absorber have been respected in the investigation. A tunable passively Q-switched laser operation is also developed with a birefringent filter plate used as an intracavity selective element. As a result, improved understanding of passively Q-switched Cr\(^4+\):YSO solid-state Cr\(^3+\):LiSAF lasers has been obtained in broadband and tunable laser operations. Characteristics of the tunable passively Q-switched Cr\(^3 + \):LiSAF laser were demonstrated to be clearly dependent on wavelength. The spectro-temporal evolution of a single pulse emitted from the passively Q-switched Cr\(^3 + \):LiSAF laser has been reported.